Prognostic value of tumour-stroma ratio in nasopharyngeal carcinoma: a two-center retrospective study - Wenze Qiu; Wenjing Chen; Jiali Jiang; Ronghui Zheng; Yawei Yuan; Xing Lv; Jiangyu Zhang (Radiation Oncology)
Abstract Background Tumour-stroma ratio (TSR) is the proportion of tumour cells relative to surrounding stroma. This study aimed to investigate the prognostic impact of TSR, and to construct a prognostic nomogram in patients with nasopharyngeal carcinoma (NPC). Methods Clinico-pathological data of 206 patients treated at Guangzhou Institute of Cancer Research, the Affiliated Cancer Hospital, Guangzhou Medical University for NPC were used as the training cohort. Assessment of TSR was performed on haematoxylin and eosin-stained slides and the correlation of TSR with survival outcomes was examined. A nomogram model comprising TSR was established and the clinical performance was evaluated by concordance index (C-index), calibration curve, time-dependent area under the curve (tAUC), and decision curve analysis (DCA). External validation was performed using cohort from Sun Yat-sen University Cancer Center (n = 343). Results High stroma ratio was proved to be an adverse prognostic factor for OS. A prognostic model integrating T stage, N stage and TSR for individual prediction of survival was constructed and graphically represented as a nomogram. Calibration curves indicated good agreement between the nomogram and actual observations. Moreover, the nomogram outperformed the commonly used staging systems. In addition, the nomogram could successfully classified patients into three different risk groups. The external validation cohort supported these findings. Conclusions TSR is a strong and independent prognostic factor for NPC patients. A nomogram that integrated T stage, N stage and TSR could serve as a precise and convenient model of risk stratification in predicting the prognosis of patients with NPC.